Diagnostic Accuracy of the HAS-BLED Bleeding Score in VKA- or DOAC-Treated Patients With Atrial Fibrillation: A Systematic Review and Meta-Analysis - Gao, Xinxing; Cai, Xingming; Yang, Yunyao; Zhou, Yue; Zhu, Wengen (Frontiers in Cardiovascular Medicine, 2021)
Background: Several bleeding risk assessment models have been developed in atrial fibrillation (AF) patients with oral anticoagulants, but the most appropriate tool for predicting bleeding remains uncertain. Therefore, we aimed to assess the diagnostic accuracy of the HAS-BLED score compared with other risk scores in anticoagulated patients with AF. Methods: We comprehensively searched the PubMed and Embase databases until July 2021 to identify relevant pieces of literature. The predictive abilities of risk scores were fully assessed by the C-statistics, net reclassification improvement [NRI] and integrated discrimination improvement [IDI] values, calibration data, and decision curve analyses. Results: A total of 39 studies met the inclusion criteria. The C-statistic of HAS-BLED for predicting major bleeding was 0.63 (0.61-0.65) in anticoagulated patients regardless of vitamin k antagonists (0.63[0.61-0.65]) and direct oral anticoagulants (0.63 [0.59-0.67]). The HAS-BLED had similar C-statistic to the HEMORR2HAGES, ATRIA, ORBIT, GARFIELD-AF, or ABC scores, but significantly higher C-statistic than the CHADS2 or CHA2DS2-VASc scores. NRI and IDI values suggested that the HAS-BLED performed better than the CHADS2 or CHA2DS2-VASc scores, and had similar or superior predictive ability compared with the HEMORR2HAGES, ATRIA, ORBIT, or GARFIELD-AF scores. Calibration and decision curve analyses of the HAS-BLED compared with other scores required further assessment due to the limited evidence. Conclusions: The HAS-BLED score has moderate predictive abilities for bleeding risks in patients with AF regardless of type of oral anticoagulants. Current evidence support that the HAS-BLED score is at least non-inferior to the HEMORR2HAGES, ATRIA, ORBIT, GARFIELD-AF, CHADS2, CHA2DS2-VASc, or ABC scores.